STUDENTS’ READING INTEREST (A CASE STUDY AT FKIP OF THE UNIVERSITY OF PASIR PENGARAIAN) - Andri Donal (JEE (Journal of English Education), 2015)
This article constitutes a discussion about the students’ reading interest at FKIP of the University of Pasir Pengaraian. It is a research report triggered from the data showed that reading was an activity disliked by Indonesian people. This reaserch can be categoried as descriptive quantitative research. In collecting data, researcher used questionnaires, observation and interviews. The result of research showed that the reading interest of FKIP-UPP students can be categorized into low level. Factors influencing students’ reading interest involving internal and external. By conducting this research, it is expected to give contribution to this institution to increase students’ reading interest.